DEGRADASI VITAMIN C DALAM JUS BUAH DENGAN PENAMBAHAN SUKROSA DAN LAMA WAKTU KONSUMSI - Vika Ayu Devianti; Ratih Kusuma Wardhani (2477 - 6165, 2018)
The degradation of Vitamin C in orange and tomato juice with sucrose addition and were storaged for 0, 30, and 60 minutes at room temperature were investigated. The level of vitamin C in juice was ensured by spectrophotometric method. The result indicated that vitamin C in sample with sucrose addition, decreased by about 0,41% (orange juice); 0,47% (tomato juice) after 30 minutes of storage; and 0,82% (orange juice); 1,19% (tomato juice) after 60 minutes of storage; while vitamin C in sample without sucrose addition, decreased by about 1,2% (orange juice); 2,12% (tomato juice) for 30 minutes of storage; and 2,45% (orange juice); 2,89% (tomato juice) for 60 minutes of storage. In conclusion, sugar addition and storage time could affect the degradation of vitamin C.